Every child is precious - Aishah Ali. (Petaling Jaya, Selangor, Malaysia : MPH Group Publishing Sdn Bhd, 2011)
Early childhood education and childcare institutions in Malaysia.
In English.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid